Avaliação da resistência flexural de fibras de vidro e cerâmicas odontológicas utilizadas como subestrutura de próteses parciais fixas - Silva, Adriana de Oliveira (2004)
The aim of this study was to evaluate the flexural strength of two fibers glass and two ceramics systems used like substructure of prosthesis fixed partial using a three point bending test. Four groups, with ten specimens and dimensions of 25+ 2mm X 2+ 0,1mm X 2+ 0,1mm (ISO 10477) to fibers glass and 25+ 5 mm X 4+ 0,25 mm X 1,2+ 0,2 mm (ISO 6872) to ceramics were prepared according to the manufacturer’s instructions, where: GI-Vectris Pontic® (Ivoclar/Vivadent), GII-Fibrex Medial® (Angelus Soluções Odontológicas), GIII- IPS Empress ®2(Ivoclar/Vivadent) e GIV- VITA In- Ceram® Zircônia. The specimens were dry stored, in plastic recipient, without light on room temperature and submitted on three point test at universal machine Instron® Corp. 2KN(crosshead speed of 0,75mm/min) and the results of the mean values of flexural strength were 516,04 + 58,44 MPa to GI , 505,23 + 85,57 MPa to GII, 182,73+ 50,33 MPa to the GIII and 442,37 + 99,89 MPa to GIV. The predominance of failure was incomplete fracture to fibers glass and complete fracture to ceramics. The results were submitted on statistical analysis, Anova (p<0,05) and there were observed differences statistically insignificant among the fibers’ group (p=0.7460) and differences statistically significant among the ceramics’ group. Concluded that fibers tested presented similar performance of flexural strength and the result suggested the possibility of fibers glass be used like alternative of alloy in good indication of clinical situation of prosthesis fixed partial. The ceramics presented not similar performance of flexural strength being VITA In-Ceram® Zircônia system able to support more load when compared with IPS Empress® 2 Ivoclar/Vivadent system.